A Method for Optimal Reconstruction of Velocity Response Using Experimental Displacement and Acceleration Signals - Bennett, Gareth (My University, 2007)
An algorithm is developed which takes advantage of the positive characteristics of integration and differentiation operations which can produce an optimal time-domain estimate of a velocity signal when a displacement and an acceleration signal are measurable. Simulations are carried out with Matlab where synthetic data is generated through solving the equations of motion of a multi-degree of freedom vibrating system. The velocity optimisation technique for velocity estimation is applied to the acceleration and displacement signals and the result is compared to the true velocity signal. A parametric analysis is carried out on the technique, as a function of extraneous noise on the simulated signals, as well as the integration and differentiation operator employed. Based on the results of the simulations, an experiment is performed where a reconstructed velocity is compared to a velocity signal measured directly using a laser vibrometer.
14th International Congress on Sound and Vibration (ICSV14)
Keywords: Smart & Sustainable Planet